The Politics of Black Representation in 'Race' (2008) directed by Abbas-Mustan. - Khanna, Palak (Tufts Archival Research Center, 2018)
The objective of this thesis is to examine the politics of Black representation in the Bollywood film ‘Race’ (2008) directed by Abbas-Mustan. In order to holistically understand the construction of Black persons in this film, the thesis considers the construction of Black identity, White identity, Indian identity, and the visual imaginings of South Africa. It also considers the relationship between White, Black, and Indian communities in South Africa from pre-apartheid times to contemporary relations as rationales for certain choices the industry has made with respect to this film. These choices include who the intended audience is, how South Africa and different racial identities are depicted, and to what ends. The thesis is a multimedia project, consisting of three parts: The first part is research that synthesizes the scholarship on the history of the Indian diaspora and of Bollywood in South Africa, the values of the Bollywood industry, the racial politics of the pre and post-apartheid era, and the relationship between South Africa and India at the time of the film’s release. The second component is a video that summarizes the film and walks the viewer through specific scenes and characters in the film that expand on a discussion of the Black representation in the film. The third component of this thesis is a written analysis of a series of fifteen interviews conducted with Black, White, and Indian viewers who watched ‘Race’ and described their experiences.